Justifications and procedures for implementing Institutional Review boards in business organizations - Giacalone, Robert A. (Journal of business ethics, 1987)
The present paper describes a number of ethical quandaries facing the implementors of motivational interventions in organizational settings. A critical analysis of the traditional solutions to these issues within the organizational literature finds them lacking for want of considering unwitting cognitive biases and self presentational doublespeak, both of which may result in the rights of research participants being underprotected. The establishment of an Institutional Review process, loosely analogized from the biomedical and behavioral science research traditions, is suggested as a means of protecting the rights of research participants as well as humanizing future motivational interventions.